USULAN PENERAPAN METODOLOGI DMAIC UNTUK MENINGKATKAN KUALITAS BERAT PRODUK DI LINI PRODUKSI FILLING: STUDI KASUS PT JAVA EGG SPECIALITIES, CIKUPA - Surbakti, Feliks Prasepta S.; Tukiran, Martinus; Natalia, Agnes (Industrial and Systems Engineering Assessment Journal (INASEA), 2011)
PT Java Egg Specialities is one of manufacturing company which produce various kinds of processed egg. Surely the company engaging consumer goods must be very concerned about quality of its products. According to the research, the nonconformance final products were found frequently. This nonconformance quality is found in filling line production in which there is weighting activity inside. The problem is sought an alternative solution with Six Sigma method. In this method research is done through 5 DMAIC steps: define, measure, analyze, improve and control. The calculation results is analyzed in analyze phase, making the fishbone diagram, and FMEA. The root causes from each factor of weight nonconformance are influence of machine setting, machines are not stable, not accurate in setting the machine, less in practice and understood, primary packaging weight has not exactly the same, presence of air bubbles, and the way of pouring emulsion.